Black public history in Chicago : civil rights activism from World War II to the cold war - Rocksborough-Smith, Ian (New Black studies series., 2018)
In civil-rights-era Chicago, a dedicated group of black activists, educators, and organizations employed black public history as more than cultural activism. Their work and vision energized a black public history movement that promoted political progress in the crucial time between World War II and the onset of the Cold War. Ian Rocksborough-Smith's meticulous research and adept storytelling provide the first in-depth look at how these committed individuals leveraged Chicago's black public history. Their goal: to engage with the struggle for racial equality. Rocksborough-Smith shows teachers working to advance curriculum reform in public schools, while well-known activists Margaret and Charles Burroughs pushed for greater recognition of black history by founding the DuSable Museum of African American History.